PENGARUH CUSTOMER ENGAGEMENT TERHADAP REPURCHASE INTENTION DENGAN CUSTOMER EQUITY SEBAGAI VARIABEL MEDIASI - Ningrum, Elzanty Dwi Kartika; Arif, Moh. Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to answer the problem of how customer engagement affects on repurchase intention, how customer engagement affect customer equity, how does customer equity affect on repurchase intention, how customer engagement affects repurchase intention through customer equity. This type of research is causality research is research that is structured to examine the possibility of a causal relationship between variables. The analytical tool used is SEM which is operated through software SmartPLS. Tests in this study used validity, reliability, and hypothesis testing. Sampling technique uses non-probability sampling with purposive sampling method. The sample size used is 120 respondents with the provision that they have used the Shopee application at least twice, are aged more than or equal to 17 years and are people of Malang City. Based on the results of testing the four hypotheses, it can be concluded that the customer engagement has a positive and significant effect on repurchase intention, the customer engagement has a positive and significant influence on customer equity, the customer equity has which is positive and significant on repurchase intention, and variables customer engagement have a positive and significant influence on repurchase intention mediated by customer equity variables.